The Research and Mechanism of Extracting Vitamin B6 Using Aqueous Two-Phase Systems - Changyu Lu; Luning Gao; Aibing Chen; Duo Li; Yahong Zhou (Journal of Chemistry)
The aim of this work is to investigate the quaternary systems which contain (polyethylene glycol/isopropyl alcohol) + ethanol + salt (Na2SO4/Na2CO3) + water to understand their liquid-liquid equilibrium (LLE) and salting-out ability and apply them to definite uses. For this purpose, phase diagrams and liquid-liquid equilibrium (LLE) data of the investigated quaternary systems were experimentally determined at 308.15, 318.15, and 328.15 K. Binodal curves were fitted to three empirical nonlinear equations, whereas tie-lines were fitted to the Setschenow-type equation and another two-parameter equation. All the models were successfully correlated with the experimental data. What is more, factors such as temperature, different organic solvent, and type of salt are studied. It was demonstrated that temperature has no influence in binodal curves and the salting-out ability follows the order Na2CO3 > Na2SO4. Finally, we chose the best system (isopropyl alcohol + ethanol + Na2CO3 + H2O) to find out the extraction efficiency when dealing with vitamin B6. The results show that when the temperature is 308.15 K and pH is 5.02, the extraction efficient can reach a top level. It serves as a theoretical basis for the extraction, separation, and purification.